The system of physical education of children and youth in educational institutions of Ukraine and Poland the second half of XIX - early XX century - Hakh R.V (Kharkov National Pedagogical University, 2010)
The problems of development and becoming of physical education of children and young people open up in educational establishments of Ukraine and Poland. Historiography of physical culture of Ukraine and Poland is analysed. Physical education in a pedagogical idea arises up as an independent object. Physical education is examined as an inalienable constituent of harmonic development of personality. Short comparative description over of development of physical education of Ukraine is brought and to Poland in an indicated period. The state of physical education of Poland is characterized westering and east of country.